Organopolysiloxane composition with expanded perlite
By using a composition containing Si-H group functionalized polysiloxane, ethylenically unsaturated group functionalized polysiloxane, hydrosilating catalyst, flame retardant and expanded perlite in the battery module, a composition is formed Compressible, thermally insulated and flame-retardant foaming materials solve the problem of insufficient thermal insulation in existing thermal barrier materials in high-energy density battery packs and improve battery safety.
Patent Information
- Application Number
- CN202280096552.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-27
- Publication Date
- 2025-01-10
AI Technical Summary
Existing thermal barrier materials are insufficient thermal insulation in high-energy density battery packs, making it difficult to prevent thermal runaway, increasing the risk of fire and explosion, and poor mechanical performance, making it difficult to meet the needs of thermal insulation, flame retardant and compressibility.
A composition is used which comprises 2-50% by weight of Si-H group functionalized polysiloxane, 1-50% by weight of water or alcohol, 10-90% by weight of ethylenically unsaturated groups Group functionalized polysiloxane, catalytic amount of hydrogenated silanization catalyst, 1-30% by weight of flame retardant and 1-15% by weight of expanded perlite to form a compressible, thermally insulated and flame-retardant foaming material .
It provides effective thermal insulation, flame retardancy and compressibility in the battery module, reduces the risk of thermal runaway and fire explosion, and meets the safety needs of high-energy density battery packs.
Smart Images

Figure BDA0005157016030000061
Abstract
Description
Background Art
[0001] The present invention relates to an organopolysiloxane composition containing expanded perlite.
[0002] Rechargeable batteries such as lithium-ion batteries (LiBs) are commonly used in a variety of applications, including electric vehicles (EVs) and grid energy storage systems. Although LiBs have the desirable properties of high energy density and stability, safety issues currently limit their usefulness. First, failure of LiB cells can be triggered due to manufacturing defects, internal short circuits, overheating, overcharging, or mechanical shock; second, the heat generated from a failed cell can propagate, causing thermal runaway in adjacent cells. The rapid pressure buildup caused by these thermal events increases the risk of fire and explosion.
[0003] Thermal runaway can be mitigated by placing a thermal barrier between the cells in the LiB module, which provides thermal insulation and flame retardancy. Commonly used thermal barriers such as aerogels, ceramic fibers, and mica boards provide such properties; however, aerogels and ceramic fibers have poor mechanical elasticity, while mica boards have poor compressibility. On the other hand, although silicone foam foam provides sufficient compressibility and is therefore suitable for low and medium energy density batteries, its thermal insulation is insufficient to prevent thermal runaway for very high energy density battery packs. Therefore, in the field of thermal barriers for rechargeable batteries, it is desirable to produce a barrier that provides thermal insulation, flame retardancy, and satisfactory compressibility. Summary of the invention
[0004] The present invention solves the need in the art by providing a composition comprising, based on the weight of the composition, a) 2 to 50 weight percent of a polysiloxane functionalized with at least two Si-H groups and having a degree of polymerization in the range of 5 to 1000; b) 1 to 50 weight percent of water, an alcohol, a diol, a polyol, or a compound containing one or more silanol groups; c) 10 to 90 weight percent of a polysiloxane functionalized with at least one ethylenically unsaturated group and having a degree of polymerization in the range of 20 to 2000; wherein the total concentration of component a, component b, and component c is in the range of 35 to 95 weight percent, based on the weight of the composition; d) a catalytic amount of a hydrosilylation catalyst; e) 1 to 30 weight percent of a flame retardant; and f) 1 to 15 weight percent of expanded perlite.
[0005] The composition of the present invention can be used to provide a foamed material that acts as a compressible, thermally insulating, and flame-retardant separator in a rechargeable battery module. DETAILED DESCRIPTION
[0006] The present invention is a composition comprising, based on the weight of the composition, a) 2 to 50 wt. % of a polysiloxane functionalized with at least two Si-H groups and having a degree of polymerization in the range of 5 to 1000; b) 1 to 50 wt. % of water, an alcohol, a diol, a polyol or a compound containing one or more silanol groups; c) 10 to 90 wt. % of a polysiloxane functionalized with at least one ethylenically unsaturated group and having a degree of polymerization in the range of 20 to 2000; wherein the total concentration of component a, component b and component c is in the range of 35 to 95 wt. % based on the weight of the composition; d) a catalytic amount of a hydrosilylation catalyst; e) 1 to 30 wt. % of a flame retardant; and f) 1 to 15 wt. % of expanded perlite.
[0007] The polysiloxane (a) functionalized with at least two, preferably at least three Si-H groups has a degree of polymerization ranging from 5 to 1000 or to 500 or to 200. The hydroxyl-containing compound (b) is preferably benzyl alcohol or a C2-C8-alkyl diol. The polysiloxane (c) functionalized with at least one, preferably at least two ethylenically unsaturated groups has a degree of polymerization ranging from 20 or 100 or 200 or 300 to 2000 or to 1500 or to 1000. The total weight percentage of component a, component b and component c, based on the weight of the composition, is in the range of 35% or 50% to 95%.
[0008] The polysiloxane functionalized with at least one ethylenically unsaturated group is preferably functionalized with two C2-C8-alkenyl groups, more preferably two vinyl or two allyl groups. The polysiloxane functionalized with at least one ethylenically unsaturated group is most preferably a polydimethylsiloxane functionalized with two vinyl groups. The polydimethylsiloxane functionalized with two vinyl groups is advantageously designed to have a viscosity in the range of 10,000 mPa·s to 50,000 mPa·s. This viscosity can be conveniently obtained by combining divinyl-functionalized polydimethylsiloxanes of different degrees of polymerization (i.e., a bimodal distribution of divinyl-functionalized polydimethylsiloxanes).
[0009] The hydrosilylation catalyst is preferably a platinum based catalyst such as chloroplatinic acid, and is used in a catalytic amount, typically in the range of 0.5 ppm to 200 ppm Pt based on the weight of the composition.
[0010] The composition also comprises from 1 wt % or 2 wt % or 3 wt % to 30 wt % or to 20 wt % or to 15 wt % of a flame retardant, which is a metal hydroxide, carbonate, hydroxide-carbonate or hydrate that releases CO2 or water or both when heated. Examples of flame retardants include Al(OH)3, Mg(OH)2, Ca(OH)2, MgCO3.3H2O (nesquehonite), Mg5(CO3)4(OH)2.4H2O (hydromagnesite), MgCa(CO3)2 (calcium carbonate), AlO(OH) (boehmite), NaHCO3 and hydrated MgSO4 (epsomite).
[0011] The composition also includes 1 wt % or 2 wt % to 15 wt % or to 10 wt % expanded perlite. Expanded perlite can be formed by rapidly heating perlite ore to a temperature in the range of 750° C. to 1000° C. The resulting expanded particles typically have a particle size of 0.03 g / cm 3 Up to 0.20g / cm 3 The average volume particle size is usually in the range of 0.1 μm to 1000 μm using a dynamic light scattering analyzer such as Beckman Coulter LS130 particle size analyzer. The density of the resulting product is 0.10 g / cm 3 or 0.15g / cm 3 Up to 0.90g / cm 3 Or up to 0.50g / cm 3 within the range.
[0012] The composition can be used to prepare polyorganosiloxane foam articles, as essentially described, for example, in US 5,358,975. Advantageously, a polysiloxane functionalized with at least three Si-H groups is contacted with a) an alcohol, a diol, a polyol or a silanol and b) a divinyl-functionalized polydimethylsiloxane in the presence of a platinum-based catalyst to form a crosslinked network of organopolysiloxanes having -Si-CH2-CH2-Si- groups and -Si-OR groups, wherein R is a structural unit of an alcohol, a diol, a polyol or a silanol (i.e., a reaction product).
[0013] It may be advantageous to prepare the foamed material using a 2-part process, wherein in a first container, a first part of a divinyl-functionalized polydimethylsiloxane; a first part of a flame retardant; a platinum-based catalyst; one or more hydroxyl-containing compounds; and a first part of expanded perlite are blended to form a Part A composition. In a second container, the remaining part of the divinyl-functionalized polydimethylsiloxane; a polymer resin blend, which is a mixture of a divinyl-functionalized polydimethylsiloxane and a crosslinked organopolysiloxane resin; the remaining part of the flame retardant; a polysiloxane functionalized with at least three Si-H groups; and the remaining part of the expanded perlite are blended to form a Part B composition. Parts A and B are then combined and mixed, and then poured between two release film sheets to form the foamed material of the present invention.
[0014] Therefore, in another aspect, the present invention is an insulating, compressible and flame retardant foam material, the foam material comprising 35 wt % to 95 wt % of polyorganosiloxane foam based on the weight of the foam material; 1 wt % to 30 wt % of a flame retardant; and 1 wt % to 35 wt % of expanded perlite; wherein the foam material has a thermal conductivity of 0.10 g / cm 3 Up to 0.90g / cm 3 Density within the range.
[0015] In yet another aspect, the present invention is a battery module comprising a housing containing an array of spatially separated battery cells and a polyorganosiloxane foam material contacting adjacent battery cells. The polyorganosiloxane foam may contact the battery cells by filling the spaces between adjacent battery cells with foam and / or by covering the battery cells with foam. The battery module may also include an end plate at the inner edge of the housing that is in direct or indirect contact with the battery cell closest to the edge. The foam material may be inserted into the cavity between adjacent battery cells and into the cavity between the battery cell and the end plate; alternatively, a foam precursor may be applied to the cell and into the cavity and then cured to form a foamed material.
[0016] The foamed materials of the present invention have been found to provide the desirable properties of thermal insulation, flame retardancy, and compressibility in battery thermal barrier applications.
[0017] In the following examples, ViMe2SiO 1 / 2 / (CH3)3Si-O 1 / 2 / SiO 4 / 2 Resin M w and M nIt was determined by gel permeation chromatography using a gpc column filled with divinylbenzene cross-linked polystyrene beads of pore type Mixed-C (Polymer Laboratory) of 5-mm diameter size. Tetrahydrofuran was used as the mobile phase and detection was performed by a refractive index detector.
[0018] Example 1 - Preparation of Foamed Organopolysiloxane Articles with Expanded Perlite Particles
[0019] The first component (Part A) was prepared by mixing together using a Flacktek Speed mixer: a dimethylvinylsiloxy terminated polydimethylsiloxane having a viscosity of about 40,000 mPas (Polymer 1, 11.0 pbw); 1) a dimethylvinylsiloxy terminated polydimethylsiloxane having a viscosity of about 1,900 mPa·s and about 0.22 wt% Vi; and 2) ViMe2SiO 1 / 2 :(CH3)3Si-O 1 / 2 :SiO 4 / 2 The structural unit ratio is 5:40:55, M n is 5000 and M w 21,400 ViMe2SiO 1 / 2 / (CH3)3Si-O 1 / 2 / SiO 4 / 2 64:36 w / w blend of 1,2-dimethyl-1,4-diol (62.9 pbw) and 1,4-butylene glycol (2.5 pbw) of 1,2-dimethyl-1,4-diol (3.2 pbw) of 1,2-dimethyl-1,4-diol (6.5 ...
[0020] A second composition (Part B) was similarly prepared by mixing together Polymer 1 (8.6 pbw), Polymer Resin Blend (49.5 pbw) and Hymod M855 aluminum hydroxide (25.6 pbw). The contents were stirred at 2000 rpm for 30 seconds, after which a linear organohydrogenpolysiloxane having a viscosity of 30 mPa·s and a 1.6 wt% SiH content (6.5 pbw) and a polydimethylorganohydrogensiloxane having a viscosity of 5 mPa·s and a 0.7 wt% SiH content (4.9 pbw) were added to the mixture and the contents were stirred at 2000 rpm for 30 seconds. Omyasphere TP-312FQ expanded perlite particles (volume average particle size of 63 μm, 4.8 pbw) were then added to the mixture and the contents were stirred at 2000 rpm for 30 seconds.
[0021] Equal amounts of Part A and Part B were then mixed and the mixture was poured between two release films (matte mylar film). The initial (pre-foaming) thickness was controlled at 0.045 inches using a nip roller. The sample was cured at 70°C for 5 minutes and then at 100°C for 15 minutes to produce a foam sheet for further testing. (Density = 0.29 g / cm 3 )
[0022] Example 2 - Preparation of Foamed Organopolysiloxane Articles with Expanded Perlite Particles The method for preparing the foamed article of Example 1 was performed in substantially the same manner except that Omyasphere 235T-FQ expanded perlite particles (volume average particle size of 124 μm, 4.8 pbw) were used in Part A and Part B. (Density = 0.31 g / cm 3 ).
[0023] Example 3 - Preparation of Foamed Organopolysiloxane Articles with Expanded Perlite Particles The method for preparing the foamed article of Example 1 was performed in substantially the same manner, except that Omyasphere 235T-FQ expanded perlite particles (9.1 pbw) were used in Parts A and B. (Density = 0.35 g / cm 3 ).
[0024] Comparative Example 2 - Preparation of Foamed Organopolysiloxane Articles with Hollow Glass Beads
[0025] The method for preparing the foamed article of Example 1 was performed in substantially the same manner except that 3M iM16K hollow glass beads (volume average particle size of 20 μm, 20 pbw) were used in Part A and Part B. (Density = 0.28 g / cm 3 ). The amount of glass beads was chosen to give a filler volume similar to that of the expanded perlite in Example 1.
[0026] Thermal insulation and flammability
[0027] The thermal insulation and flammability of the foams prepared as described in the examples were tested using a hot plate set on a hydraulic press. The hot plate was set at 600°C with an insulator on top of the surface. Four thermocouples (type K) were fixed to an aluminum heat sink (4"×4"×0.47") using Kapton tape. The sample (4"×4") was then placed and fixed to the heat sink using Kapton tape. Another thermocouple (type K) was attached to the sample surface using Kapton tape. The insulator was removed from the hot surface, and the sample attached to the heat sink was quickly placed on the hot surface so that the sample surface faced the hot plate surface and the Al heat sink faced the opposite side. The pressure was quickly increased to 355kPa. The interface temperature between the hot plate surface and the sample surface and the interface temperature between the sample surface and the heat sink were recorded using a data logger. Once the time reached 300 seconds, the pressure was released and the test was terminated. Sample surface temperatures of <300°C were considered acceptable. No observable flames throughout the test were considered acceptable flame retardancy.
[0028] hardness
[0029] Measure hardness using a Shore 00 durometer. Place the test specimen on a hard, flat surface. Then press the indenter of the Shore 00 durometer onto the specimen, making sure it is parallel to the surface. Read the hardness during firm contact with the specimen. A hardness of <80 is considered acceptable.
[0030] Compression force
[0031] The compressive force was measured using a TA.HDplus Texture Analyzer equipped with a 100kg load cell, a 40mm diameter aluminum probe, and a flat heavy-duty aluminum substrate. The silicone foam sample was cut into a circle using a 1" diameter die cut and placed between the substrate and the probe. The probe was initially set at the same height as the sample thickness and lowered at a rate of 1 mm / sec until the pressure reached a maximum. The sample thickness and pressure were recorded as a compression force curve. The pressure was recorded at 30% of the initial sample thickness. A compression force of <500 kPa was considered acceptable.
[0032] Foam density
[0033] The foam density was calculated based on the average thickness and weight of two foam samples having a diameter of 1 inch.
[0034] The properties of the expanded perlite-filled organopolysiloxane article were compared to two other foams: Comparative Example 1, which is a commercial organopolysiloxane article (COHRlastic silicone foam, available from Stockwell Elastomerics) that is similar in construction to the Example foam except that it does not contain expanded perlite; and Comparative Example 2, which is a foam containing 3M Glass Bubbles iM16K hollow glass microspheres.
[0035] Table 1 summarizes the performance characteristics of the foams of Examples 1 to 3, commercial comparative foams, and foams containing hollow glass microspheres. Density in g / cm 3 Measurements; hardness is measured in Shore 00 units; compression (Force) is measured in kPa at 30% compression; temperature at 600°C (T after 300 seconds) refers to the sample surface temperature after 300 seconds; and flammability refers to the observability of flames during the thermal insulation test.
[0036] TP-312-FQ refers to Omyasphere TP-312-FQ expanded perlite; 235T-FQ refers to Omyasphere 235-T-FQ expanded perlite; and iM16K refers to 3M Glass Bubble iM316K hollow glass microspheres.
[0037] Table 1 - Properties of organopolysiloxane products
[0038]
[0039]
[0040] Table 1 shows that the foam of the present invention containing expanded perlite passed all tests, while the sample without expanded perlite (Comparative Example 1) failed the thermal insulation test, and the sample with hollow glass microsphere filler (Comparative Example 2) failed the compression force test.
Claims
1. A composition comprising a) 2 to 50 wt% of a polysiloxane functionalized with at least two Si-H groups and having a degree of polymerization in the range of 5 to 1000, based on the weight of the composition; b) 1 to 50 wt% of water, an alcohol, a diol, a polyol, or a compound containing one or more silanol groups; c) 10 to 90 wt% of a polysiloxane functionalized with at least one ethylenically unsaturated group and having a degree of polymerization in the range of 20 to 2000; wherein the total concentration of component a, component b, and component c is in the range of 35 to 95 wt% based on the weight of the composition; d) a catalytic amount of a hydrosilylation catalyst; e) 1 to 30 wt% of a flame retardant; and f) 1 to 15 wt% of expanded perlite.
2. The composition of claim 1, wherein the polysiloxane functionalized with at least two Si-H groups is functionalized with at least three Si-H groups; the total concentration of component a, component b and component c is in the range of 50% to 80% based on the weight of the composition; the concentration of the flame retardant is in the range of 2% to 20% by weight based on the weight of the composition; and the concentration of the expanded perlite is in the range of 2% to 10% by weight based on the weight of the composition.
3. The composition according to claim 2, wherein the polysiloxane functionalized with at least one ethylenically unsaturated group is a divinyl-functionalized polydimethylsiloxane having a degree of polymerization ranging from 100 to 1000.
4. The composition according to claim 3, wherein the flame retardant is one or more flame retardants selected from the group consisting of Al(OH)3, Mg(OH)2, MgCO3·3H2O, Mg5(CO3)4(OH)2·4H2O, MgCa(CO3)2, AlO(OH), NaHCO3 and hydrated MgSO4.
5. The composition of any one of claims 1 to 4, wherein the divinyl functionalized polydimethylsiloxane is a bimodal distribution of divinyl functionalized polydimethylsiloxanes having a combined viscosity in the range of 10,000 mPa·s to 50,000 mPa·s.
Citation Information
Patent Citations
Organosiloxane elastomeric foams
US5358975A